Factors related to Nursing workload in the Oncology assistance provided to hospitalized women - Talita Balaminut; Gabriela Alves Godoy; Elenice Valentim Carmona; Ariane Polidoro Dini (Universidade de São Paulo, 2024)
Objective: to evaluate the Nursing workload and its related factors in the assistance provided to hospitalized women with gynecological and breast cancers, according to the Nursing Activities Scores adapted for cancer patients. Method: a cross-sectional and epidemiological study. The participants were women with gynecological and/or breast cancer, over 18 years of age, and hospitalized for a minimum period of 24 hours. The following was collected from the medical records: sociodemographic and clinical data, Karnofsky Performance Status and workload, according to the adapted Nursing Activities Score. The factors related to workload were analyzed by means of multiple linear regression. Results: the mean Nursing Activities Scores was 29.3%, denoting seven hours of daily care per patient. The factors related to workload differed according to the breast or gynecological cancer diagnosis (β=-0.01; p<0.001), clinical or surgical treatment (β=-0.03; p<0.001) and functional capacity at admission (β=0.07; p<0.001), as per the Karnofsky Performance Status. Conclusion: there was greater workload for the care of women with gynecological cancer undergoing clinical treatment and with lower functional capacity at admission. The findings reveal directions for optimization of resources and improvements in work processes and flows, in order to promote a favorable work environment and good quality assistance.